A comparative study on the effects of niacin plus atorvastatin with that of fenofibrate plus atorvastatin in dyslipidemia - Selim Ahmed; A. K. M. Mosharrof Hossain; Sudhangshu R. Dey; A. K. M. Akhtaruzzaman; Mushammath Morium Siddika (Bangladesh Pharmacological Society, 2008)
The study was designed to evaluate and compare the effects of co-administration of atorvastatin (10 mg) either with niacin (1 g) or fenofibrate (200 mg) daily for 12 weeks in 67 coronary heart disease patients with dyslipidemia. There were no significant differences among the two groups (35 patients in Group I and 32 patients in Group II) in serum lipid profile except in level of triglyceride reduction where fenofibrate-atorvastatin combination yielded significant (p<0.001) results. SGPT level significantly raised and fasting blood glucose level decreased in fenofibrate-atorvastatin treated group than niacin-atorvastatin combination. Serum creatinine level decreased in niacin-atorvastatin treated group compared to fenofibrate-atorvastatin, but the changes was within normal limit. This study shows that both combinations are equally effective in dyslipidemia. Although, fenofibrate-atorvastatin combination decreased more triglyceride and niacin-atorvastatin combination appeared safer considering some adverse effects.